An investigation of user satisfaction with human resource information systems in Public Universiti of Malaysia - Ibrahim, Hadziroh; Othman, Nur Zahiyah; Hassan, Zuraida; Ibrahim, Zahidah (2017)
The study sought to examine the influence of system factors on user satisfaction amongst employee, particularly the administrative staffs in one of public universities in Malaysia, which is Universiti Utara Malaysia (UUM).The application of human resource information system (HRIS) in the UUM is known as PERSIS.At the end of the data collection period, a total of 132 questionnaires were used for analysis.The regression result indicated that system factors are significantly related to HRIS success. Support and ease of use have strongly related to user satisfaction compared to other factors. Therefore, a few suggestions have been proposed to enhance the efficiency and effectiveness of PERSIS in UUM.